Factors influencing youth involvement in the bodaboda transport business in Dodoma City, Tanzania - Tossy, Titus (CV. Literasi Indonesia, 2026)
This research was conducted in two designated wards, specifically Miyuji and Mnadani, in Dodoma city, with an emphasis on the determinants of youth participation in the Bodaboda transportation enterprise, examining socioeconomic and demographic variables, as well as other motivational factors. This investigation used a sample of 175 participants and employed a cross-sectional research design to collect primary data. Data collection methodologies incorporated interviews and documentary analysis. The gathered data were subjected to both descriptive and inferential statistical analyses. The findings indicated that marital status and household size significantly influence youth engagement in the Bodaboda sector. In contrast, age, educational attainment, breadwinner status, and cohabitation with parents exhibited negligible influence on youth participation in the Bodaboda enterprise. Furthermore, sources of income and employment status significantly affected youth involvement in the Bodaboda business. In contrast, access to credit, initial capital requirements, and Bodaboda loans had minimal influence on youth engagement in this sector. Additionally, activities such as using WhatsApp, engaging with social media, the type of mobile device youths use, watching television, reading newspapers, and listening to the radio were significantly correlated with youth participation in the Bodaboda enterprise. Consequently, it is recommended that the central government establish supportive programs to enhance youth access to education and facilitate their transition from the Bodaboda sector to more formalized business ventures. The government should formulate policies and initiatives to combat poverty by improving educational access and financial resources, investing in youth skill development programs, strengthening job security policies, and promoting youth entrepreneurship.